Proton acceleration from a pair of laser pulses target interaction - Obaydur Rahman; Zheng-Mao Sheng (AIP Advances)
An attempt has been made to generate a high-quality mono-energetic proton beam from a double-layer hydrogen target irradiated by a pair of sequential low-intensity lasers. The two-dimensional particle-in-cell simulation code Opic has been used for this investigation. In this scheme, the pre-target is highly dense while the rear-target is critically dense. Compared to the other two single-laser cases, we found a significant enhancement of the peak and cutoff energies, the number of higher energy accelerated protons, and a reduction of the energy spread and beam divergence. The peak energy, cutoff energy, and energy spread are ∼305 MeV, ∼400 MeV, and ∼12.7%, respectively. The enhancement of the proton acceleration is attributed to the enhancement of the laser energy absorption due to the long-time laser–plasma interaction. The dependences of the proton acceleration on the time intervals and pre-targets have also been investigated.